Conexões e interações do processo de criação no ensino de design do produto: modos de desenvolvimento do pensamento - Farias, Marcelo José Oliveira de (2018)
Design is a creative, projective and strategic activity aimed at offering the best adaptation and interaction of the human being with himself, with others and with the world. A interdisciplinary and transdisciplinary area of knowledge that integrates both theoretical and practical knowledge, as well as concrete and abstract concepts, by means of projects, which involve processes of observation, imagination, analysis, configuration and representation, intended to develop technical and formal solutions to enable its production, commercialization and use. Design teaching means the context in which the construction of this way of thinking is build up. From this premise comes the restlessness and central issue that moves and drives this scientific research within the program of postgraduate studies in communication and semiotics: "How does a design project interact with the student's actions in their creative strategies in network strategies in the domain of education?" Therefore, the empirical object that emerges from this dynamic between the variable and the invariable of the question are the interactions and connections between the design project and the student's projective activities in their creative networked strategies. In order to develop this research, we defined the case-exploratory and ethnographic study based on the observation and analysis of two undergraduate design courses located in the city of São Paulo: design course at the University of São Paulo / USP and design course of University Senac, through observation in the classroom, recording of the creation process documents and interviews with teachers of design and other correlated subject areas. The set objectives are to understand the paradigmatic, detonating, organizing, directional and communicational aspects of creation, which activate thought and act as lines of forces, establishing unstable connections and interconnections through dialogues and interlocutions that produce interactions, influences, mutual exchanges and shared, between elements and individuals, making arise and unleash the maneuvers and articulations of thought in the process of creation